2009
DOI: 10.1057/jibs.2008.101
|View full text |Cite
|
Sign up to set email alerts
|

From the Editors: Student samples in international business research

Abstract: The JIBS Statement of Editorial Policy states that ''Empirical submissions utilizing undergraduate student samples are usually discouraged.'' Wording is important here -''usually'' does not imply ''always.'' This statement suggests that while student samples are appropriate, in principle, undergraduate ones are not, except in unusual situations. The purpose of this From the Editors column is to discuss the pros and cons of student samples in international business (IB) research. Are student samples appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
156
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(169 citation statements)
references
References 12 publications
1
156
1
1
Order By: Relevance
“…As our hypotheses are not specific to ISAs but to more general interpersonal relationships and pertain to relative stable characteristics of human nature (Bello et al, 2009), two arguments support our decision to use business students, as respondents. First, the use of a homogeneous sample of business students allows us to improve internal validity (Croson et al, 2007).…”
Section: Samplementioning
confidence: 80%
See 1 more Smart Citation
“…As our hypotheses are not specific to ISAs but to more general interpersonal relationships and pertain to relative stable characteristics of human nature (Bello et al, 2009), two arguments support our decision to use business students, as respondents. First, the use of a homogeneous sample of business students allows us to improve internal validity (Croson et al, 2007).…”
Section: Samplementioning
confidence: 80%
“…In addition, as our hypotheses pertain to fundamental processes concerned with basic and relative stable characteristics of human nature (Bello et al, 2009), which are not specific to ISAs but to more general interpersonal relationships, business students who represent future managers are a pertinent population to study response strategies in a strategic alliance context. Furthermore, the use of a homogeneous sample of business students allows us to improve internal validity (Croson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This finding furthermore suggests that behavioural and decision modelling based on student responses (cf. Janssen and Ostrom 2006) might also be applicable in the broader context of practical decision making, despite the apparent demographic and socio-economic differences between students and other groups in society (Bello et al 2009). However, notwithstanding the similarities in beliefs and expectations of current and future managers, we also found that factors such as age and education of respondents significantly determined their sensitivity and intended responses to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…In other disciplines, such as psychology, experiments are commonly conducted using student samples, and there may be a false perception by authors that JIBS does not publish research using student samples. For some IB topics, such as the study of the cross-cultural perceptions of advertising strategies or global career choices, student samples may be quite appropriate (Bello et al, 2009). The choice of sample alone should not discourage IB scholars from using the experimental method.…”
Section: Experimentation In Ib Researchmentioning
confidence: 99%